Blended Learning-Based Model Training Using Google Classroom - Asyari, Lutfi; Ahmad, Jajang; Mulyadin, Nurdin (Fakultas Kewirausahaan Universitas Garut, 2023)
This awareness has driven the need to develop a blended learning training model that focuses not only on delivering material but also on improving students' digital skills, enabling them to better adapt to online learning. The descriptive method used in the blended learning-based training model using Google Classroom is designed to ensure that each step in the training implementation is carried out systematically and structured. In this service, the total training time is devoted to discussions, Q&A sessions, and hands-on practice, allowing students to directly apply the theory they have learned in a practical context. As a result, participants demonstrated a deeper understanding of the concepts taught. In this service, providing the right tools to facilitate online learning and training for instructors creates a more productive learning environment.